Controversy in Christendom: Celibacy and Reverend Fathership in Catholic Church - Balogun, Olaniran O.E.; Ojelabi, I. K. (NIU Journal of Humanities; Vol 5 No 1 (2020): KIU Journal of Humanities, Vol. 5 No. 1, March 2020, 2020)
This question refers to Jesus's teaching found in the Gospel of St. Matthew, when He said, "Do not call anyone on earth your father. Only one is your Father, the One in heaven" (Mt 23:9). Taken literally, we would have to wonder why we do use this title "Father" when Jesus seems to forbid it. First, we must remember the context of the passage. Jesus is addressing the hypocrisy of the Scribes and the Pharisees the learned religious leaders of Judaism. Our Lord castigates them for not providing a good example; for creating onerous spiritual burdens for others with their various rules and regulations; for being haughty in exercising their office, and for promoting themselves by looking for places of honor, seeking marks of respect and wearing ostentatious symbols. Basically, the Scribes and the Pharisees had forgotten that they were called to serve the Lord and those entrusted to their care with humility and a generous spirit. Given that context, Jesus says not to call anyone on earth by the title "Rabbi," "Father," or "teacher," in the sense of arrogating to oneself an authority which rests with God and of forgetting the responsibility of the title. As Jesus said, only the heavenly Father is the true Father, and only the Messiah is the true teacher and rabbi. In a similar vein, Jesus said, "Whoever loves father or mother, son or daughter, more than Me is not worthy of Me" (Mt 10:37). Keywords : Controversy, Christendom, Celibacy, Reverend Fathership, Catholic Church